Religious experience in post modernity and the phenomena of acceleration in comparison with pre-modern and modern temporalities - Helmut Renders (Horizonte, 2015)
Late modernity is characterized by processes of technological acceleration, the acceleration of social changes and the pace of life. These transformations of temporal structures lead not only to a restructuration of work and private everyday life, economic structures and public policies, but also to religious experience. The article begins with the understanding of the dynamic of interaction between religious experiences and its respective temporal contexts. Different kinds of religious experience are related to specific characters of antique, modern and late modern temporality. During Antiquity, religious experiences capable to handle the immutable order of all things, for example, self-denial was favored. In modernity, processional religious metaphors become popular, however still encompassing life as a whole and still in a communitarian and personal perspective, as the creation of the category “ordo salutis” or metaphor "way of salvation". In turn, the process of acceleration of time in late modernity seems to emphasis on instant experiences, a kind of emotionally heartfelt fullness, as is the case of ecstatic experiences in general and the "baptism in the “Holy Spirit” in particular.